Inflammation and infections in unreported chronic obstructive pulmonary disease exacerbations - Calderazzo, Maria Adelaide (Int J Chron Obstruct Pulmon Dis, 2019)
Purpose: COPD patients often do not report acute exacerbations to healthcare providers – unreported exacerbations. It is not known whether variances in symptoms, airway obstruction, aetiology and inflammatory responses account for differences in reporting of COPD exacerbations. The aims of the study were to compare symptoms, lung function changes, aetiology and inflammatory markers between exacerbations that were reported to healthcare providers or treated, with those that were unreported and untreated. Patients and methods: We recruited a cohort of COPD patients and collected clinical data and blood and airway samples when stable and during acute exacerbations. Virological and bacterial analyses were carried out and inflammatory markers measured. Results: We found no differences in symptoms, lung function, incidence of infection and inflammatory markers between reported and unreported exacerbations. Subjects who reported all exacerbations had higher BODE scores, lower FEV(1) and more exacerbations compared with those who did not. Conclusion: The failure to report exacerbations is not related to the severity, aetiology or inflammatory profile of the exacerbation. Patients with less severe COPD and less frequent exacerbations are less likely to report exacerbations. The decision to report an exacerbation is not an objective marker of exacerbation severity and therefore studies that do not count unreported exacerbations will underestimate the frequency of clinically significant exacerbations. A better understanding of the factors that determine non-reporting of exacerbations is required to improve exacerbation reporting. Trial registration: ClinicalTrials.gov Identifier: NCT01376830. Registered June 17, 2011